Factors Predicting Cardiotoxicity of Chemotherapy in Breast Cancer Patients at 1 Year - Soison, Witsupha; Phligbua, Warunee; Wattanakitkrileart, Doungrut; Parinyanitikul, Napa (Journal of The Royal Thai Army Nurses, 2026)
The objective of this study was to investigate the predictive power of age, comorbidities, educational level, health behaviors, residential area, and health literacy on the occurrence of cardiotoxicity within one year of chemotherapy in breast cancer patients. A total of 136 breast cancer patients who had completed 1 year of chemotherapy were recruited. Data were collected using structured questionnaires covering personal and clinical information, health behaviors, residential area, and health literacy. The quality of the instruments was assessed using Cronbach’s alpha coefficients, which were .97, .85 and .85 respectively. Data analysis was conducted using binary logistic regression. The findings revealed that age was a statistically significant predictor of cardiotoxicity. Specifically, increasing age was associated with a 1.088-fold increase in the likelihood of developing cardiotoxicity (OR = 1.088, 95% CI: 1.021–1.160, p < .05). The findings of this study can be utilized as a basis for surveillance and reduction of the incidence of chemotherapy-induced cardiotoxicity. Furthermore, they serve as foundational nursing information for promoting patients’ knowledge and understanding of the disease, including the potential signs and symptoms of cardiotoxicity.